Quality of Life and Psychological Effects of Port-Wine Stain: A Review of Literature - Wanitphakdeedecha R; Ng JNC; Yan C; Manuskiatti W; Sudhipongpracha T; Jantarakolica T (Dove Medical Press, 2021)
Rungsima Wanitphakdeedecha,1,2 Janice Natasha C Ng,1 Chadakan Yan,1 Woraphong Manuskiatti,1 Tatchalerm Sudhipongpracha,2 Tatre Jantarakolica3 1Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 2College of Interdisciplinary Studies, Thammasat University, Bangkok, Thailand; 3Faculty of Economics, Thammasat University, Bangkok, ThailandCorrespondence: Rungsima WanitphakdeedechaDepartment of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, 2 Pran-nok Road, Bangkok, 10700, ThailandTel + 66-2419-4333Fax + 66-2411-9922Email rungsima.wan@mahidol.ac.thIntroduction: Port-wine stain (PWS) is a congenital malformation that does not resolve spontaneously and can cause a physiological or psychological burden to the patients. At present, most of the studies done on PWS are focused on the treatment rather than the quality of life and psychological effects of the disease.Material and Methods: A comprehensive literature search was done in MEDLINE using PubMed database, Embase®, and Cochrane. All observational studies were included in this review.Results: A total of 17 relevant articles with 2,135 PWS patients were included in this review. There were 36 measurement tools used to assess the quality of life and the psychological effects among PWS patients. The results showed that patients with facial PWS had a significant negative effect on their quality of life and had also suffered from psychological disabilities. The PWS lesion tends to worsen with age and may cause further adaptation problems towards the social environment, especially in children.Conclusion: Early treatment, psychological assistance, and patient support are the key management in improving the quality of life of patients with PWS. Quality of life must be regularly assessed together with the improvement of treatment.Keywords: port-wine stain, quality of life, psychological effects